2020
DOI: 10.1002/ajoc.202000402
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Regioisomeric Bithiophenes in the Oxidative Synthesis of Tetrathieno‐Fused π‐Expanded Fluorenes and Their Characterization

Abstract: Differently-linked bithienyl-attached fluorenes have been synthesized. While the oxidative photodicyclization of 2,3'-bithiophene-containing fluorene was successful to yield tetrathieno-fused regioisomeric π-expanded fluorenes, the reaction with 2,2'-bithiophene-containing fluorene was very sluggish. Interestingly, the connectivity in bithiophenes appears to determine the (photo)reactivity. On the one hand, under mild Scholl conditions, 2,3'-bithiophene-containing fluorene yielded a highly regioselective produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…Attempts with Rathore's method using DDQ (2,3‐dichloro‐5,6‐dicyano‐1,4‐benzoquinone) and protic/Lewis acid [50] on 1 a–3 a led to an uncharacterized complex mixture of products. This observation is analogous to the literature reports dealing with thiophenes having substituent‐free (α‐ and β‐) positions [16,37,38] . Based on the enormous success in multiple C−C bond formation with polyphenylenes, we resorted to optimizing Scholl oxidative FeCl 3 /DCM conditions [18,19] at room temperature (rt, 28 °C) for isomeric substrates 1–3 as the next step.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Attempts with Rathore's method using DDQ (2,3‐dichloro‐5,6‐dicyano‐1,4‐benzoquinone) and protic/Lewis acid [50] on 1 a–3 a led to an uncharacterized complex mixture of products. This observation is analogous to the literature reports dealing with thiophenes having substituent‐free (α‐ and β‐) positions [16,37,38] . Based on the enormous success in multiple C−C bond formation with polyphenylenes, we resorted to optimizing Scholl oxidative FeCl 3 /DCM conditions [18,19] at room temperature (rt, 28 °C) for isomeric substrates 1–3 as the next step.…”
Section: Resultssupporting
confidence: 69%
“…This observation is analogous to the literature reports dealing with thiophenes having substituent-free (α-and β-) positions. [16,37,38] Based on the enormous success in multiple CÀ C bond formation with polyphenylenes, we resorted to optimizing Scholl oxidative FeCl 3 /DCM conditions [18,19] at room temperature (rt, 28 °C) for isomeric substrates 1-3 as the next step. We found that using nitromethane with FeCl 3 was not necessary here.…”
Section: Oxidative Cyclization Of Batsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyfluorenes (PFs) are a kind of blue light-emitting materials with excellent properties. , PFs with wide band gaps, excellent thermal and chemical stability, and high quantum efficiency are garnering an increasing amount of research interest. , In particular, studies on 9,9-disubstituted fluorene-based polymers have demonstrated that such PF derivatives can effectively enhance the solubility and processability of PFs. The 9,9-Dihexyl-2,7-dibromofluorene (F6-Br) with a typical structure of 9,9-disubstituted fluorene-based halohydrocarbon (Figure ) is an important intermediate product in the synthesis of 9,9-disubstituted fluorene-based polymers. The purity of F6-Br has a significant impact on the characteristics of the generated polymer in this type of synthesis reaction, and side reactions caused by impurities in the reactants often result in low-quality polymers with a low molecular weight and poor regioregularity. Small levels of fluorenone in the reactants, for example, can increase the likelihood of ketone defects forming in the produced polymers, lowering the color purity, and decreasing the device longevity, while the partial substitutional oxidation of fluorenes produces these fluorenones, which can be efficiently reduced by monomer purification . The solvent/antisolvent (SAS) method has been one of the efficient methods to purify organic molecules for advanced applications. The solubility of materials in various organic solvents is an important parameter for solution treatment and crystallization. Therefore, it is critical to investigate the dissolution and purification of F6-Br in various solvents for advanced applications.…”
Section: Introductionmentioning
confidence: 99%